A Measure of Interdependence: Skill in the Supply Chain. Issue 4 (November 2018) - Forbes, Allison
Economic development strategies often target high-skill and high-wage industries and occupations, but the relationship between skills and wages is uneven and complicated. This study offers a skill-centered, industry-level overview of this uneven landscape. Familiar data sources (input–output tables, industry–occupation matrices, and occupational skill profiles) are used to analyze skill demand across the U.S. automotive cluster. The author shows that the automotive industry depends on the high-level manufacturing skills of intermediate goods suppliers and highlights that the lower wages in these and lower-tier supply sectors may impede skill regeneration and upgrading. Economic and workforce development practitioners can use this analysis to begin or reinvigorate skill-centric conversations with employers in high- and low-skill sectors. Industry leaders can use it to demonstrate the extent to which larger firms rely on the skills of their supply network and to motivate investments in skill development across the supply chain.